Pengaruh Inisiasi Menyusui Dini Terhadap Ikterus Neonatorum - Siskawati Umar; Efri Leny Rauf; Hindun Khairin Nisaa Koem (Kampurui Jurnal Kesehatan Masyarakat, 2021)
Neonatal jaundice is a clinical condition in newborns characterized by a yellow color that appears on the skin, sclera, mucous membranes, or other organs caused by the buildup of bilirubin. Neonatal jaundice is generally physiological if it lasts more than 48 hours and less than 14 days. This literature research aims to determine the effect of early breastfeeding initiation on neonatal jaundice. The method used is a descriptive narrative method in the form of a literature study that is carried out by searching the literature through Google Scholar, Pubmed, Biomedcentral and text books. The literature used is the publication of 2011-2020 both nationally and internationally and is relevant to the topic taken. The results of a literature study in 14 journals and 4 books found that there was an effect of early initiation of breastfeeding on neonatal jaundice. Based on the research, it can be concluded that early initiation of breastfeeding can prevent neonatal jaundice